Selection for the improvement of maize yield under moisture deficits - Fischer, K.S.; Edmeades, G.O.; Johnson, E.C. (Elsevier, 1989)
Throughout the lowland humid tropics, unpredictable periods of non-protracted drought are responsible for significant reductions in maize (Zea mays L.) yield, and losses may be disastrously large if drought coincides with the period around flowering. This study was conducted to develop and evaluate a selection procedure to improve the drought resistance of maize populations grown under limited moisture supply, particularly around flowering. Eighty-five full-sib progenies of the tropical lowland population Tuxpeno were grown under three soil moisture-deficit treatments at a site in Mexico without rainfall during the season. The treatments were; mild (normal irrigation); medium (irrigation to field capacity soon after emergence and again 10 days after flowering); and severe (irrigation to field capacity soon after emergence only) soil moisture-deficits. Mean yields were 6120, 4330 and 1560 kg ha−1, respectively, under the three treatments. There was significant genotype (progeny) × soil moisture-deficit interaction for grain-yield. Yield under the severemoisture-deficit was significantly correlated with a measure of the rate of leaf and stem extension (). Tnterval between male and female flowering () and rate of foliar senescence (). These indices were used along with grain-yield in a selection index. To test its usefulness, experimental varieties formed from progenies selected for yield per se unde the different soil moisture-deficit treatments and for a divergence (index-tolerant and index-susceptible) of performance using the selection index were grown under conditions similar to those of the initial progeny evaluation. The drought-tolerant variety (selected for yield and favourable adaptive traits) outyieldeall others by 500 kg ha−1 under the severe moisture-deficit but not at the expense of yield under the well-watered conditions. Recurrent selection for these traits under similar moisture-deficits was practised among 250 full-sib progeny in this population for three cycles. Canopy temperature, determined by infrared thermometry prior to flowering, was highly correlated () with yield under severe moisture-deficits, and was included in the selection index after the second cycle. After three cycles of improvement with a 33% progeny-selection intensity, evaluation under the same soil moisture-deficits showed that grain-yield increased by 1.8, 7.8 and 21.6%, or 320, 420 and 410 kg ha−1 cycle−1 under the mild, medium and severe moisture-deficits, respectively. There were significant changes in the drought-adaptive traits, but there was no significant change in days-to-flowering under the well-watered conditions.